The coexistence of tourism and mining: a strategic framework for cross-sectoral interaction. Issue 17 (22nd November 2018) - Moyle, Brent D.; Moyle, Char-lee J.; Bec, Alexandra
Abstract : The tourism and resources sectors are often observed to come into conflict. Yet little research has examined the complex interactions between the two sectors, specifically the strategies for building resilient rural regions. Consequently, this research explores the coexistence of the tourism and resources sectors in the Gladstone and Roma regions in Queensland, Australia. A total of 78 in-depth interviews revealed a complex network of interactions between the tourism and resource sectors, outlining deficiencies in previous theoretical premises on sectoral interaction. Key findings revealed three key synergies including resources sector investment, resources sector multipliers and induced travel, and formal and informal partnerships. Strategies to enhance the coexistence also emerged focused on reducing the negative impacts of the co-evolution process, improving industrial tourism products and developing trust, partnerships and a joint vision between the two sectors. A theoretically informed management framework for future interaction is subsequently proposed for testing and application in other contexts.